PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA KELAS I SDN 08 KOTO BARU - Antik Estika Hader; Rauldatul Husni; Laila Nurjannah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the learning process that has not shown interesting progress and has not been able to encourage active participation from students. This situation directly negatively affects students' learning achievement in English subjects which is still relatively low. Therefore, efforts are needed to develop more effective and interesting learning methods to improve student learning outcomes in these subjects. This study aims to obtain information on how much influence the Teams Games Tournament (TGT) type cooperative learning model has on the English learning outcomes of grade I elementary school students. This research is an experimental research that uses pre-experimental research design, with the form of one group pretest-posttest design. The research location was SDN 08 Koto Baru, Koto Baru District, Dharmasraya Regency. The research sample consisted of 24 students who were all grade I students. The data collection instrument used was a multiple choice test of 10 items, which had been tested for validity and reliability. The results showed that the average pretest score was 76.25 and the average posttest score was 88.75. Description of the research data from the analysis of pretest and posttest data, using the Wilcoxon test shows a significance value of 0.001 <0.05. From the criteria, if the significance <0.05 then H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant effect of the application of the Teams Games Tournament (TGT) type cooperative learning model on the English learning outcomes of grade I students of SDN 08 Koto Baru.